Geodesign in Pampulha cultural and heritage urban area: Visualization tools to orchestrate urban growth and dynamic transformations - Zyngier, Camila M.; Moura, Ana Clara; Palhares, Rogério; Carsalade, Flávio (Rozwój Regionalny i Polityka Regionalna, 2016)
This paper discusses the role of visualization in Geodesign methodology considering its applications in the case study of the region of Pampulha in Belo Horizonte, Minas Gerais, Brazil. In order to consider the opinion of the participants, their efforts were recorded in different steps of the process, at different stages of Geodesign iterations, and different possibilities of visualization were tested. The methodology of Geodesign was applied in different applications and with different tools. The goal was to determine whether different techniques and tools used in the process of Geodesign contributed to improved understanding of data and problem context, and to derive guidelines for improved Geodesign techniques and tools.